2020
DOI: 10.3389/fpubh.2020.00389
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of a Mental Health App in Apprentice Workers: A Pilot Study

Abstract: Background: Young people are at heightened risk for mental health problems. Apprenticeships are common pathways into the workforce at a critical developmental period. However, in some cases the working conditions for apprentices present significant challenges to mental wellness. As apprentices are unlikely to utilize traditional services, eHealth and mHealth interventions are a useful means of delivering interventions to this group. The aim of the current paper is to: (1) qualitatively explore the utility of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…A mixed methods study was conducted with 54 apprentices from September to November 2017. This study was part of a larger qualitative study exploring the mental health challenges of apprentices in the workplace [8], their healthy coping strategies, and their attitudes toward using an app to support their mental health (the focus of this paper); the larger study also included focus testing of the Headgear smartphone app (a behavioral activation and mindfulness app that was initially designed to improve the mental health of workers in male-dominated industries) [29]. All participants were reimbursed with an Aus $40 (US $27.97) Visa gift card for their time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixed methods study was conducted with 54 apprentices from September to November 2017. This study was part of a larger qualitative study exploring the mental health challenges of apprentices in the workplace [8], their healthy coping strategies, and their attitudes toward using an app to support their mental health (the focus of this paper); the larger study also included focus testing of the Headgear smartphone app (a behavioral activation and mindfulness app that was initially designed to improve the mental health of workers in male-dominated industries) [29]. All participants were reimbursed with an Aus $40 (US $27.97) Visa gift card for their time.…”
Section: Methodsmentioning
confidence: 99%
“…While apprentices were asked about their smartphone and well-being app use, we did not explore other aspects of digital literacy in this study. Finally, expectations of a mental health app and preferred features were not directly explored during the focus groups, but were instead explored during the user-testing phase of the Headgear app [29].…”
Section: Limitationsmentioning
confidence: 99%
“…Therefore, although there are similarities with school students, being part of the work force rather than taking part in a purely educational environment means apprentices face some different experiences. For example, the transition from school to work is a developmental challenge that may present risk factors to mental health [21,22]. Indeed, a survey of Austrian apprentices from 2015 showed that apprentices assess their current state of health as significantly worse than high school students [23].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the utility of apps has been largely explored, although most of the studies aim to access the usability of specific apps using qualitative approaches and surveys. For instance [ 23 ], explore the utility of an existing mental health app through group discussions and surveys [ 24 ]. examine the usability and inter-rater reliability of an app for the System for Observing Play and Recreation in Communities using observers to collect data [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“… [ 19 ] Identify the barriers to mask-wearing in Spain Survey Young, educated, unconcerned with being infected, and an introverted personality – the typical profile of citizens resistant to face-masking. [ 23 ] Explore the utility of an existing mental health app within an apprentice population and evaluate the usability, acceptability, feasibility, and preliminary efficacy of a modified version of the app. Group discussions and survey The app was a well-received intervention when adapted to young apprentices.…”
Section: Literature Reviewmentioning
confidence: 99%